Ultrasound, magnetic resonance imaging and radiography of the finger joints in psoriatic arthritis patients. (18th March 2021) - Polachek, Ari; Furer, Victoria; Zureik, Mirna; Nevo, Sharon; Mendel, Liran; Levartovsky, David; Wollman, Jonathan; Aloush, Valerie; Tzemah, Reut; Elalouf, Ofir; Anouk, Marina; Berman, Mark; et al.
Abstract: Objectives: To report the discrepancies and agreements between US, MRI and radiography of the hand in PsA, and to compare the sensitivity and specificity of US and radiography to MRI as the gold standard imaging study in PsA. Methods: All of the 100 prospectively recruited consecutive PsA patients underwent clinical assessment and concomitant radiographic, US and MRI studies of the MCP, PIP and DIP joints of one hand. Synovitis, flexor tenosynovitis, extensor paratenonitis, erosions and bone proliferations were identified and scored. All readers were blinded to clinical data, and agreement was calculated based on prevalence-adjusted bias-adjusted kappa (PABAK). Results: The prevalence of synovitis, flexor tenosynovitis, extensor paratenonitis and erosions was similar for US and MRI, while that of bone proliferation was significantly increased in US and radiography compared with MRI ( P   <  0.001). The absolute agreement between US and MRI was good-to-very good for synovitis (85–96%, PABAK = 0.70–0.92), flexor tenosynovitis (93–98%, PABAK = 0.87–0.96) and extensor paratenonitis (95–98%, PABAK = 0.90–0.97). Agreement between US, MRI and radiography was 96–98% (PABAK = 0.92–0.97) for erosions and 71–93% (PABAK = 0.47–0.87) for bone proliferations. Sensitivity of US with MRI as gold standard was higher for synovitis (0.5–0.86) and extensor paratenonitis (0.63–0.85) than for flexor tenosynovitis (0.1–0.75), while the specificity was high for each pathology (0.89–0.98). Conclusion: There is very good agreement between US and MRI for the detection of inflammatory changes in finger joints in PsA. US, radiography and MRI have a good-to-very good agreement for destructive changes.